(untitled) (Research, Society and Development, 2022)
This study aims to analyze the predominant risk factors for the development of acute kidney injury in hospitalized patients with COVID-19. This is an integrative review of retrospective and prospective cohort studies and observational studies, with a search carried out in PubMed and Virtual Health Library databases with the keywords "SARS-CoV-2", "acute kidney injury", and "risk factors", selecting those that answered the guiding question “what are the predictors and risk factors for the development of acute kidney injury in hospitalized patients with COVID-19?”. Following this research and applying the year of publication and language filters, 39 articles were initially selected. After exclusions, 7 articles were included in the present review, which had their quality evaluated and their data collected using the PRISMA methodology. In all selected articles, the statistical significance of 11 risk factors was verified, such as high D-dimer, serum creatinine, C-reactive protein, increase in the number of leukocytes, decrease in lymphocytes, advanced age, gender, high body mass index, hypertension, diabetes and chronic kidney disease. After analysis of the selected articles, it was found that the most frequent risk factors for an AKI outcome are mainly advanced age, chronic kidney disease and elevated C-reactive protein on admission. Overall, these factors are risk indicators and require greater attention from professionals to provide an effective therapeutic approach and prevent serious outcomes.